Preparation of ZnO hybrid nanoparticles by ATRP. (19th December 2016) - Ding, Hangjun; Yan, Jiajun; Wang, Zongyu; Xie, Guojun; Mahoney, Clare; Ferebee, Rachel; Zhong, Mingjiang; Daniel, William F.M.; Pietrasik, Joanna; Sheiko, Sergei S.; Bettinger, Christopher J.; Bockstaller, Michael R.; et al.
Abstract: Zinc oxide (ZnO) is a wide bandgap semiconductor material that has attracted widespread interest as particle filler in polymer nanocomposite materials. However, its applications have been hindered by the limited dispersibility and surface-modification techniques. Herein, three distinct approaches for the synthesis of polymer-tethered ZnO hybrid materials are compared in terms of uniformity and yield of the particle-brush product: "grafting-from", "grafting-onto", and "grafted-copolymer template" methods. In the "grafting-from" method, pristine ZnO nanoparticles (NP) were first functionalized with atom transfer radical polymerization (ATRP) initiators followed by grafting-from process to form poly(methyl methacrylate) (PMMA) or poly(styrene- co -acrylonitrile) (PSAN) tethered polymer chains. In the "grafting-onto" method, PMMA- b -PAA (poly[acrylic acid]) and PSAN- b -PAA diblock copolymers were prepared and attached onto the surface of ZnO NPs using sonication bath. For the "grafted-copolymer template" method, PSAN- b -P t BA-Br (poly[ tert -butyl acrylate]-Br) macroinitiators were crosslinked with divinylbenzene (DVB) to form PSAN- b -P t BA-PDVB core-shell star polymers. After hydrolysis to form PSAN- b -PAA-PDVB star polymers, the functional stars were used as polymer templates for the synthesis of ZnO NPs within the PAA-core of the stars. Core-shell molecular bottlebrushes with PAA- b -PS block-copolymer side chains were also used as anisotropic analogues of star template to prepared worm-like ZnO particles. Several ZnO precursors, zinc nitrite, zinc 2-ethylhexanoate, and zinc acetate were evaluated as precursors of ZnO. Conditions were identified that enable the synthesis of polymer-tethered ZnO with excellent size uniformity and dispersion characteristics using the star-template method. Graphical abstract: Highlights: ZnO hybrids were prepared via "grafting-from", "grafting-onto", & "templating". ZnO hybrids with relatively high size uniformity and dispersibility were obtained. ZnO hybrid nanoparticles were prepared using molecular bottlebrush templates.